An investigation of the existing business models of Small Private Security Companies in Kenya: a Case Study of mark patrol (Kenya) Limited - Kibua, Darren (Strathmore University, 2013)
This dissertation investigates the existing business models of the small private security company (PSC) in Kenya, guided by the fact that PSCs operate in an industry with high growth potential and negligible regulatory hindrance. The broad objective of this study was to understand the existing business models and the challenges of business growth faced by small PSCs. This was done through a case study of Mark Patrol (Kenya) Limited (MPKL), a small third tier PSC, which was the only security company that was willing to share its business information. The dissertation begins by providing an overview of the private security industry (PSI) in general and the PSC sector in particular. Then it reviews available literature on the concepts of a firm, business growth, measurement of business growth, the different stages of business growth, governance and management. From the literature review a conceptual framework is developed. The framework identifies the macro-environment, governance, management, the competitiveness of small PSCs and the competitiveness of the PSC sector as the principal factors influencing the business growth of small PSCs. To achieve its objectives, the study analyzes qualitative and quantitative data collected from the internal and external environment of MPKL using questionnaires, interviews, focus groups and various sources of secondary data. The analysis concludes that the macro-environment and competitiveness of the PSC sector do not significantly inhibit the business growth of MPKL. It further identifies a lack of both good governance structures and managers with adequate administrative capacity at MPKL, which results in a principal-agent dilemma. Finally, the dissertation provides recommendations on the strategies that MPKL, and many other similar small PSCs, can adopt to improve their business models and prospects for growth.
A dissertation submitted to Strathmore Business School, Strathmore University, in partial fulfillment of the requirements for the Degree of Master of Business Administration.
Keywords: Business modelling; Small private securities; Kenya; Mark Patrol